Mercadoria e significações: práticas das editoras independentes no Brasil - Bitencourt, João Vitor da Silva (2022)
This paper seeks to dissect the independent publishing market in Brazil and the meanings attached to it by its publishers, inserted in the context of the crisis of the publishing market, as well as the pandemic of COVID-19. Thus, we seek to understand how in the face of an oscillating publishing scenario and through the pandemic, what are the paths taken by Brazilian independent publishers in this context? As a general objective of the dissertation, we sought to analyze how the independent publishing market in Brazil is configured, in a context of instability of the publishing market and pandemic. As specific objectives, we sought to reflect on the actors of the independent publishing market; to investigate the meanings attached to independent production by these actors; and to investigate how the pandemic affected the independent publishing niche. We propose a discussion about what it is to be independent through the analysis of the works of Cristina Lyra Couto De Souza (2011), José de Souza Muniz Jr (2016), Leandro Müller (2017), Raquel Vitorelo (2019), Julia Contreiras (2019), Samara Mírian Coutinho (2020) and Maria Luísa Acioli Falcão de Alencar (2020). The methodological steps taken in the work were inspired by the practices and conceptualizations of netnography through Kozinets (2014). To this end, we conducted a participant observation as a way of entering the field in the reading and translation group promoted by Edições Tijuana. Online surveys aimed at independent publishers, publishers, and independent collectives were carried out as a data collection tool and a way to establish a first contact with publishers. Subsequently, we conducted interviews to further develop some issues arising from the surveys and other points that emerged from the publishers themselves. We present a systematization after the reports obtained in the interviews, through the concepts of capitals by Bourdieu (2008; 2018) and the rationalities of consumption by Canclini (1992; 2008), to understand how producers see the independent in Brazil, and how they navigate their market issues in relation to their artistic and personal production. Thus, we can notice how collectivity is very present in the scenario of independent publications, with a strong sense of community. It is possible to infer a common profile among the publishers with a high academic background in their majority, a factor that needs to be pondered when questioning the structures of the movement. Economic factors appear both as an almost constant difficulty for the publishers, but also that it is accepted as part of their daily lives, without expecting so much in the way of return in this sense, that they value other forms of return much more. Finally, the question about what it is to be independent in Brazil remains without a definitive answer, it follows a constant and ever-changing search, with several possible definitions.